2019
DOI: 10.2478/sbe-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

Investments, Economic Growth and Employment: VAR Method for Romania

Abstract: Economic growth can be seen as an effect of both fiscal policies and different legislative norms applied at national and macroeconomic level. Investments are a determining factor in the evolution of socio-economic life, influencing also the employment rate. This paper aims to identify the influence of investments on economic growth and employment using the vector autoregressive model (VAR). Based on the quarterly data from Romania, between the first quarter of 2000 and the second quarter of 2018, the Granger c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Thus, this reduced impact of unemployment on the economic activity effect of human capital corroborates with the studies of (Adeleye et al, 2022;Agasisti and Bertoletti, 2022;Fatimah et al, 2021;Majidi, 2017;Matousek and Tzeremes, 2021;Shidong et al, 2022;Zafar et al, 2019). Despite arguing that the Okun law is not valid in the proportion foreseen by the author, however, it cannot be denied that the described effect is observed, which agrees with the studies (Altunöz, 2019;Daniela et al, 2019;Dritsakis and Stamatiou, 2018;Ikechukwu, 2017;Nagel, 2015;Okur et al, 2018;Pasara and Garidzirai, 2020;Sharma and Sharma, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, this reduced impact of unemployment on the economic activity effect of human capital corroborates with the studies of (Adeleye et al, 2022;Agasisti and Bertoletti, 2022;Fatimah et al, 2021;Majidi, 2017;Matousek and Tzeremes, 2021;Shidong et al, 2022;Zafar et al, 2019). Despite arguing that the Okun law is not valid in the proportion foreseen by the author, however, it cannot be denied that the described effect is observed, which agrees with the studies (Altunöz, 2019;Daniela et al, 2019;Dritsakis and Stamatiou, 2018;Ikechukwu, 2017;Nagel, 2015;Okur et al, 2018;Pasara and Garidzirai, 2020;Sharma and Sharma, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…The results of the estimates indicated that unemployment is positively affected by economic growth, according to the authors, and for this sample, a 1% increase in GDP caused a 0.8% drop in unemployment (Okur et al, 2018). For the Romanian economy, it was observed that investment promotes economic growth and implicitly is responsible for generating more jobs (Daniela et al, 2019). The existing relationship between unemployment and economic activity was investigated in Nigeria by (Ikechukwu, 2017) between 1970-2014.…”
Section: Literature Reviewmentioning
confidence: 81%
“…The Wald lag exclusion test was used to examine the possibility of lag elimination of any variable in the VAR system. The Wald test is a safety test for the number of lags chosen from the selection criteria [86]. Based on the results of the Wald test shown in Table 6, we found that the selected variables used in the VAR were significant (p-value < 0.05).…”
Section: Var Diagnostic Resultsmentioning
confidence: 96%